PAI Curriculum Innovation In Public College To Improve Student Competency - Muhammad Arifin Arifin (Ilomata International Journal of Social Science, 2021)
Innovation is defined as renewal in the face of change or improvement. Change is a shift in position or situation that is likely to result in a significant increase. Practical The curriculum is changed due to several factors, for example the development of science and technology. There is a possibility that the benefits of a predetermined or expected curriculum change could go wrong. Changing the curriculum in a very short period of time is considered a failure in certain cases, but is also believed to be an attempt to achieve improvement. Curriculum reform involves several components or several factors. Curriculum change cannot be successful without being complemented by those who are supported by component systems. Changes that are partial in nature will automatically waste energy, time, funds, and energy. In addition, changes to the curriculum are more focused on the curriculum itself and ignore other aspects; such as teachers / lecturers, students, methods, media funds, etc. will potentially fail. Therefore it needs serious consideration and reasonable reasons with the desire and total involvement of the components of the education system, so as to increase competence.